Individual health discount rate in patients with ulcerative colitis - Waljee, Akbar K.; Morris, Arden M.; Waljee, Jennifer F.; Higgins, Peter D.R. (Inflammatory bowel diseases, 2011)
In cost-effectiveness analysis, discount rates are used in calculating the value of future costs and benefits. However, standard discount rates may not accurately describe the decision-making of patients with ulcerative colitis (UC). These patients often choose the long-term risks of immunosuppressive therapy over the short-term risks of colectomy, demonstrating very high discount rates for future health. In this study we aimed to measure the discount rate in UC patients and identify variables associated with the discount rate.MethodsWe surveyed patients with UC and patients who were postcolectomy for UC to measure their valuations of UC and colectomy health states. We used Standard Gamble (SG) and Time-Trade-Off (TTO) methods to assess current and future health state valuations and calculated the discount rate.ResultsParticipants included 150 subjects with UC and 150 subjects who were postcolectomy for UC. Adjusted discount rates varied widely (0%-100%), with an overall median rate of 55.0% (interquartile range [IQR] 20.6-100), which was significantly higher than the standard rate of 5%. Within the normal range of discount rates, patients' expected discount rate increased by 0.80% for each additional year of age, and female patients had discount rates that averaged ≈8% less than their age-matched counterparts and approached statistical significance.ConclusionsThe accepted discount rate of 5% grossly underestimates UC patients' preference for long-term over short-term risk. This might explain UC patients' frequent choice of the long-term risks of immunosuppressive medical therapy over the short-term risks of colectomy. (Inflamm Bowel Dis 2011;)